413 Cervical conization and sentinel lymph node for fertility preservation in early low-risk cervical cancer. Less is better?. (13th November 2020) - Esteban, A; Lucchini, S; Ferreyra, H; Goldsman, MG; Fochini, M; Heredia, F
Abstract : Introduction: Radical trachelectomy is the standard treatment to preserve fertility in early stage cervical cancer. Several studies reported a low rate of parametrial spread in selected groups of patients. There is no a consensus of low-risk tumors: size <2 cm, squamous or adenocarcinoma histology, and no evidence of lymph vascular space invasion (LVSI). Conization could be an oncologically safe option. The aim of this study was to evaluate the oncological and obstetric data of patients with low risk early cervical cancer treated with conization and sentinel lymph node (SLN) ± complete pelvic lymphadenectomy (CPL) to preserve fertility. Methods: Double-institution retrospective study of patients with low risk cervical cancer treated with conization and SLN/CPL from September 2013 to January 2020. Inclusion criteria: FIGO (2018) stages 1A1 with LVSI to IB1, invasion depth ≤10 mm, squamous or adenocarcinoma histology, negative margins, age < 45 years, fertility desire. Results: Included 27 patients; median age was 31.33 years (23–39). Seven patients had stage IA1 with LVSI (25.9%), 10 (37.04%) IA2 and 10 (37.04%) IB1. We performed nine (33.33%) conization and CPL and 18 (66.66%) conization + SLN ± CPL. Bilateral SLN detection was 100%. We didn´t have intraoperative complications. No recurrences have been diagnosed in 37.37 (5–81) months of follow up. Eight pregnancies have been documented with 1 first trimester miscarriage, 5 term deliveries and 2 on-going gestations. Conclusion: Conization and SNL ± CPL in early stage cervical cancer has favorable prognostic features and could be oncologically safe in a selected group of patients.